Damaged Neocortical Perineuronal Nets Due to Experimental Focal Cerebral Ischemia in Mice, Rats and Sheep - Härtig, Wolfgang; Mages, Bianca; Aleithe, Susanne; Nitzsche, Björn; Altmann, Stephan; Barthel, Henryk; Krueger, Martin; Michalski, Dominik (Frontiers in Integrative Neuroscience, 2017)
As part of the extracellular matrix (ECM), perineuronal nets (PNs) are polyanionic, chondroitin sulfate proteoglycan (CSPG)-rich coatings of certain neurons, known to be affected in various neural diseases. Although these structures are considered as important parts of the neurovascular unit (NVU), their role during evolution of acute ischemic stroke and subsequent tissue damage is poorly understoodAnd only a few preclinical studies analyzed PNs after acute ischemic stroke. By employing three models of experimental focal cerebral ischemia, this study was focused on histopathological alterations of PNs and concomitant vascular, glial and neuronal changes according to the NVU concept. We analyzed brain tissues obtained one day after ischemia onset from a) mice after filament-based permanent middle cerebral artery occlusion, b) rats subjected to thromboembolic middle cerebral artery occlusion and c) sheep at 14 days after electrosurgically induced focal cerebral ischemia. Multiple fluorescence labeling was applied to explore simultaneous alterations of NVU and ECM. Serial mouse sections labeled with the net marker Wisteria floribunda agglutinin (WFA) displayed largely decomposed and nearly erased PNs in infarcted neocortical areas that were demarcated by up-regulated immunoreactivity for vascular collagen IV. Subsequent semi-quantitative analyses in mice confirmed significantly decreased WFA-staining at the ischemic border zone and a relative decrease in the directly ischemia-affected neocortex. Triple fluorescence labeling throughout the three animal models revealed up-regulatedcollagen IV and decomposed PNs accompanied by activated astroglia and altered immunoreactivity for parvalbumin, a calcium-binding protein in fast-firing GABAergic neurons which are predominantly surrounded by neocortical PNs. Furthermore, ischemic neocortical areas in rodents simultaneously displayed less intense staining of WFA, aggrecan, the net components neurocan, versican and the cartilage link protein as well as markers in net-bearing neurons such as the potassium channel subunit Kv3.1b and NeuN. In summary, the consistent observations based on three different stroke models confirmed that PNs are highly sensitive constituents of the NVU along with impaired associated GABAergic neurons. These results suggest that PNs could be promising targets of future stroke treatment, and further studies should address their reorganization and plasticity in both stabilizing the acute stroke as well as supportive effects during the chronic phase of stroke.